Mathematical Connection Ability of Junior High School Students in Solving Story Problems on Probability - Annisa Fachraini Siregar; Maydiyanti Putri; Naufal Hilmiy; Aminda Salsabillah; Suripah Suripah (Fakultas Tarbiyah Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
This study aims to describe the mathematical connection abilities of ninth-grade junior high school students in solving story problems on probability. The aspects examined include connections among mathematical concepts, links to other disciplines, and relevance to daily life. A descriptive qualitative approach was applied to 22 students at a junior high school located in Tapung Hilir District. Data were collected through essay-based tests and semi-structured interviews, with three students selected to represent high, medium, and low levels of mathematical connection ability. Results showed that 9 students were categorized as high, 9 students as medium, and 4 students as low. Students in the high category demonstrated a strong conceptual understanding, although they lacked systematic problem-solving strategies. Medium-level students showed comprehension yet required guidance. Low-level students struggled to interpret story problems and relate them to probability concepts. These findings emphasize the need for contextual learning and structured practice to enhance students’ mathematical connection abilities.